Metamorphosis - Christin Bolewski (2011)
Metamorphosis – Christin Bolewski (2007; 5:32) ‘Growth gets confronted with destruction, aesthetic beauty with rotten ugliness.’ Using the possibilities of modern video processing and animation techniques the motif of a traditional still life gets fragmented. Different parts of the image are arranged running simultaneously forward or backward, in fast motion or being looped – the still life starts to “breathe”.